1999
DOI: 10.1016/s0022-5347(01)61639-2
|View full text |Cite
|
Sign up to set email alerts
|

Bone Mineral Density in Men Treated With Synthetic Gonadotropin-Releasing Hormone Agonists for Prostatic Carcinoma

Abstract: The use of Gn-RH agonists in men may induce an accelerated bone loss. Further studies are needed to confirm these results and to evaluate the incidence of osteoporotic fractures in men treated with Gn-RH agonists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 268 publications
(62 citation statements)
references
References 16 publications
2
59
0
1
Order By: Relevance
“…In the present study, although the degree of BMD decrease was observed in both, the CAB group and GnRH group without any statistical differences between groups (p = 0.8636, Table 2), the total BMD score of L-spine showed significantly smaller change in the CAB group, as compared to the GnRH group (p < 0.05, Table 2). Many studies on bone mineral loss in patients with prostate cancer have shown that BMD decrease of L-spine ranges from 2.40% to 4.80% post-ADT for ≤12 months, which was similar to our results of 2.58% in the CAB group and 4.37% in the GnRH group14151617181920212223.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the present study, although the degree of BMD decrease was observed in both, the CAB group and GnRH group without any statistical differences between groups (p = 0.8636, Table 2), the total BMD score of L-spine showed significantly smaller change in the CAB group, as compared to the GnRH group (p < 0.05, Table 2). Many studies on bone mineral loss in patients with prostate cancer have shown that BMD decrease of L-spine ranges from 2.40% to 4.80% post-ADT for ≤12 months, which was similar to our results of 2.58% in the CAB group and 4.37% in the GnRH group14151617181920212223.…”
Section: Discussionsupporting
confidence: 91%
“…In the literature review of prospective studies, a wide range of BMD changes is influenced in patients who received ADT by different types of ADT, period of ADT, and patient ethnicity or presence of bone metastasis12131415161718192021. In the present study, although the degree of BMD decrease was observed in both, the CAB group and GnRH group without any statistical differences between groups (p = 0.8636, Table 2), the total BMD score of L-spine showed significantly smaller change in the CAB group, as compared to the GnRH group (p < 0.05, Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Once used primarily to treat metastatic prostate cancer, ADT is now used as adjuvant therapy for locally advanced or high-risk localized prostate cancer and as treatment of biochemical failure after primary therapy (1–3). Because most men with prostate cancer receive the diagnosis at an older age and because androgen deficiency is associated with low bone mineral density (BMD), men with prostate cancer who receive treatment with ADT are at particularly increased risk for osteoporosis and related fractures (49). …”
mentioning
confidence: 99%
“…By improving bone health, older patients with prostate cancer may have less need for opiate medications, orthopedic procedures, and less risk of fractures, with the occurrence of any of these potentially causing a dramatic shift in a patient's ability to live independently and contribute to their risk of morbidity and mortality. Beyond its beneficial anti-cancer effects, ADT worsens bone health as it contributes to osteoporosis, compounding the morbidity of this disease in terms of bone health [48]. Providers should monitor vitamin D levels and encourage calcium and vitamin D supplementation as indicated to maintain good bone health in patients on ADT or with bone metastasis.…”
Section: Bone Therapymentioning
confidence: 99%